35 Identification Of Fusarium Wilt Disease On Red Curly Chili (Capsicum Annuum L.) and Its Control At Hegarmanah Valley, Cipinang Village - Nurkarimah, Ilmi; Rinda Nurapriliani; Yulia Regita; Fuad Hilmi (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Curly red chili (Capsicum annuum L.) is an important horticultural commodity because its consumption will continue to increase every year, so it is considered to have the potential to continue to grow. Wilting disease caused by the fungus Fusarium oxysporum is a common disease that attacks curly red chili plants. The method used in preparing this report is descriptive qualitative method through observation, interviews and literature studies. Observations on curly red chili plants that were attacked by Fusarium wilt showed symptoms of wilting from the stem to the leaves of the plant. Severe attacks can cause plants to die and experience crop failure.